Beach vegetation as an indicator of human impacts in arid environments: Environmental conditions and landscape perception in the Canary Islands. (15th June 2019) - Peña-Alonso, Carolina; García-Romero, Levi; Hernández-Cordero, Antonio I.; Hernández-Calvento, Luis
Abstract: Human occupancy of beaches is an important cause of environmental and landscape transformations, some of which are identifiable through vegetation analysis. Commonly, arboreal vegetation has been socially perceived in a positive way, as it contributes to the creation of environments appreciated as beautiful and natural. This type of vegetation has been recreated in urban coastal areas worldwide, including those located in arid environments where it is not always common or endemic to these areas. The typology of plant species, human impacts on beach environments, and the social perception of vegetation contrast were analyzed to understand the landscape influence and human impact on beach environments from arid regions. The study was carried out on 12 beaches with different degrees of human occupation (4 urban, 4 semi-urban and 4 natural) in Gran Canaria island (Spain). The results indicate that the number of exotic and ruderal (first to colonize human disturbed environments) species increases with human occupation of the beaches. A greater number of arboreal species were identified on urban beaches, while shrub and herbaceous species were more common on less occupied beaches (semi-urban and natural). However, when surveyed, the users of semi-urban and natural beaches, considered that arboreal vegetation compose a more attractive landscape than other with herbs or shrubs, even though tree species appear occasionally on these types of beaches. This inconsistency identifies a conflict of values between the development and conservation of beaches in arid environments. This study can be used to establish environmental sustainability strategies on beaches. Conservation and environmental information about ecosystem services related with indigenous plant species is and important issue for integrated management on beaches from arid regions, especially those that may be urbanized in the near future. Highlights: This research analyzes beach vegetation and social preferences in arid environments. The study was conducted in urban, semi-urban and natural beaches. Exotic vegetation related to trees, increases with human occupation. Native vegetation, as herbs or shrubs, is less preferred than exotic tree species. Results could be useful for future planning of beaches from arid environments.